Integrating Green Intellectual Capital into Sustainable Business Practices for Ecopreneurship at Pertamina Fuel Terminal BBM PROPER Biru - Syahidun, Syahidun; Zainal, Veithzal Rivai; Siswanti, Indra; Nawangsari, Lenny Christina (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study examines the roles of Green Organizational Capital (GOC) and Green Relational Capital (GRC) in enhancing Corporate Sustainability Performance (CSP), with Green Innovation (GI) as a mediator and Knowledge Management Systems (KMS) as a moderator within Pertamina's Fuel Terminal operations. A qualitative approach was used, employing semi-structured interviews, document analysis, and observations. Data were analyzed thematically to uncover patterns and relationships. GOC and GRC significantly impact CSP, with GI serving as a critical mediator. However, KMS has a limited moderating role, indicating gaps in integrating knowledge systems into sustainability practices. This study contributes to the understanding of Green Intellectual Capital (GIC) and identifies areas for improving KMS in sustainability efforts. Organizations should strengthen internal structures, external relationships, and knowledge management to promote green innovation and long-term sustainability. The study offers a novel framework integrating GIC, GI, and KMS in the energy sector, providing actionable insights for emerging economies.